Factors associated with decision-making on fertility among rural women in the central district of Tamil Nadu - Geetha Jeganathan; Sampath kumar Srinivasan; Senthilkumar Ramasamy; Pitchaimani Govindharaj (BMC Research Notes)
Abstract Introduction Fertility decision-making is an important factor affecting the Total Fertility Rate. Good communication between partners encourages shared decision-making and equal participation. Women’s decision-making plays an important role in determining their reproductive health and fertility behaviour. Therefore, this study aimed to assess the decision-making of rural women on fertility. Methods A household survey was conducted by using a multi-stage sample with 407 married women aged 18–45 years, having at least one child and living in Tiruchirappalli District, Tamil Nadu were recruited for this study. A semi-structured questionnaire was used to collect data about the demographic status and decision-making related to fertility. Results Of the 407 participants, 70% were aged between 26 and 40 years, 73% were working as farmers and labourers and 77% were living in nuclear families. In decision-making on the usage of contraception, 25%, 27% and 27% of their decision were taken by themselves, their spouse, and both the participants and their spouse respectively. In spacing of childbirth, 53% took decisions concurrently with their husband. Among the participants, 40%, of their intake of food in the pre-and post-natal period was decided by them and 44% of women preferred the institutional delivery for childbirth by themselves. Conclusion The study reveals that women tend to prefer sharing and involving their spouses in making decisions on fertility-related issues. Additionally, they exhibit greater support during the pre- and post-natal periods for women.